(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Helmi H, Kusmiadi R, Mahardika RG, Karsiningsih E. 2024. Diversity of fungi and dynamics of ethanol concentration during fermentation of porang (Amorphophallus oncophyllus). Biodiversitas 25: 542-552. Fermentation can be an alternative to process porang (Amorphophallus oncophyllus). As one of the fermentation products, ethanol can degrade starch and consequently increase the purity of glucomannan in porang flour. However, ethanol can also inhibit the growth of microorganisms that play a role in fermentation. This study aimed to determine the ethanol concentration and investigate the fungal diversity during the fermentation of porang tubers. Ethanol analysis was analyzed by Headspace Gas Chromatography coupled with flame ionization detection, and Starch content was analyzed by colorimetric method. Fungal metagenome was amplified at the Internal transcribed spacer (ITS) region of nuclear DNA (rDNA) and followed by sequencing using Oxford Nanopore Technology (ONT). The result showed that the ethanol concentration increased during 48 hours of fermentation, followed by decreased starch content. The highest fungal diversity index occurred at 48 hours of fermentation. Ethanol and fungal enzymatic activity can degrade the starch. During fermentation, the Candida parapsilosis population increased until 24 hours after fermentation. Cyberlindnera subsufficiens population increased at 48 hours fermentation until 72 hours fermentation. Fungal diversity and ethanol concentration had decreased at 72 hours of fermentation, so porang fermentation should be stopped at 48 hours. Candida parapsilosis could be the candidate of starter for fermentation porang due to the capability of this species to produce ethanol to degrade starch.